IMPLEMENTASI DAN PEMBATASAN ASAS KEBEBASAN BERKONTRAK (FREEDOM OF CONTRACT) DALAM MELAKUKAN PERJANJIAN DI DALAM MASYARAKAT UNTUK MENJAMIN ADANYA KESEIMBANGAN DAN KEPASTIAN HUKUM - Hartana; Yasmiati, Ni Luh Wayan (Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
This article aims to provide knowledge and increase understanding to the public regarding the implementation and limitations of the principle of freedom of contract in making agreements in society to ensure balance and legal certainty. An agreement is an agreement by which one or more parties bind themselves to one or more people. The application of the principle of freedom of contract cannot be used freely. There are several restrictions imposed by legislative regulators. Because if there are no restrictions, it will result in arbitrariness in making the contents of the agreement which can harm the interests of the parties involved in the agreement, so that the concept of social justice for all parties, which is one of the goals of freedom of contract, will not be realized. The method used in this community service process is by conducting outreach and outreach with the community through focus group discussions. Implementing and limiting the principle of freedom of contract is a crucial step in maintaining balance and legal certainty in society. Although this principle provides flexibility to parties involved in an agreement, there is an important need to ensure that individual rights and societal interests are protected without compromising contractual flexibility. A wise balance must be found. Legal certainty in the agreement must be prioritized. Adequate regulation should ensure that the weaker party to an agreement is protected from harmful practices.